An unusual case of postoperative ascites after cesarean section - Sandhu, Namrita; Singh, Sanjay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Post-operative ascites following caesarean section is rarely reported in pregnancy. Ascites has multiple etiologies including malignancies, liver cirrhosis, intraperitoneal infections and trauma. Authors report a case of post-operative ascites following caesarean section performed at around 37 weeks of gestation. The patient was normotensive. The diagnosis and treatment of ascites as well as the pregnancy outcome is presented. Literature review of ascites in pregnancy is discussed as well. This case was that of an idiopathic ascites with no definitive cause. An allergic or inflammatory peritoneal reaction may be the most likely cause for this complication.